Being-in-Creation : Human Responsibility in an Endangered World - Treanor, Brian; Benson, Ellis, 1960-; Wirzba, Norman (Book collections on Project MUSE., 2015)
"What is the proper relationship between human beings and the more-than-human world? This philosophical question, which underlies vast environmental crises, forces us to investigate the tension between our extraordinary powers, which seem to set us apart from nature, even above it, and our thoroughgoing ordinariness, as revealed by the evolutionary history we share with all life. The contributors to this volume ask us to consider whether the anxiety of unheimlichkeit, which in one form or another absorbed so much of twentieth-century philosophy, might reveal not our homelessness in the cosmos but a need for a fundamental belongingness and implacement in it"--